2016
DOI: 10.1002/2016gl069621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of photochemical processing of DOC on the bacterioplankton respiratory quotient in aquatic ecosystems

Abstract: Many studies assume a respiratory quotient (RQ = molar ratio of CO2 produced to O2 consumed) close to 1 when calculating bacterioplankton respiration. However, evidence suggests that RQ depends on the chemical composition of the respired substrate pool that may be altered by photochemical production of oxygen‐rich substrates, resulting in elevated RQs. Here we conducted a novel study of the impact of photochemical processing of dissolved organic carbon (DOC) on RQ. We monitored the bacterial RQ in bioassays of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…Bacterioplankton respiration is a key process for converting organic carbon to CO 2 in aquatic ecosystems (Williams and Del Giorgio, 2005). This mineralization of DOC driven by microbial respiration is accompanied by O 2 consumption, often with an assumed RQ of 1, yet this quotient depends on substrate properties and metabolic states (Dilly, 2003;Berggren et al, 2012;Allesson et al, 2016). Similar to the CO 2 production rates in experimental set-up 1 and the higher O 2 consumption rates in P-spiked samples in experimental set-up 2 could represent a situation with higher BGE than in P-limited samples.…”
Section: Experimental Validation Of Driversmentioning
confidence: 99%
“…Bacterioplankton respiration is a key process for converting organic carbon to CO 2 in aquatic ecosystems (Williams and Del Giorgio, 2005). This mineralization of DOC driven by microbial respiration is accompanied by O 2 consumption, often with an assumed RQ of 1, yet this quotient depends on substrate properties and metabolic states (Dilly, 2003;Berggren et al, 2012;Allesson et al, 2016). Similar to the CO 2 production rates in experimental set-up 1 and the higher O 2 consumption rates in P-spiked samples in experimental set-up 2 could represent a situation with higher BGE than in P-limited samples.…”
Section: Experimental Validation Of Driversmentioning
confidence: 99%
“…A weakness with this approach is the uncertainty related to the RQ value used for unit conversion to carbon. Studies in unproductive lakes in different boreal regions have reported average bacterioplankton RQs of 1.2 (Berggren et al ) or ~ 2 (Cimbleris and Kalff ), and RQs as high as ~ 3 have been experimentally achieved by feeding bacteria with UV light treated partially oxidized DOC (Allesson et al ). Considering that partial UV oxidation followed by microbial decay could be a major pathway of organic carbon decay in tundra region freshwaters (Cory et al ), it is possible that the RQ and thus also the DOC decay rates in this study were underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic field study of the RQs of freshwater bacterioplankton showed large variability (1.2 ±0.45) with a significant negative correlation between RQ and in situ O 2 concentration and pH and a significant positive correlation between RQ and in situ pCO 2 (Berggren et al, 2011). Bacterioplankton RQs were low (average 0.81) in net autotrophic freshwater systems where reduced substrates derived from phytoplankton excretion are likely to dominate and higher (average 1.35) in net heterotrophic freshwater systems where oxidized substrates such as organic acids formed by photochemical processes could occur (Allesson et al, 2016). However, due to the low rates of oxygen consumption and CO 2 production by marine plankton, and the precision of methods to measure changes in dissolved inorganic carbon (DIC; ∼1-2 mmol m −3 ), there has not been a systematic field study of the magnitude and variability of marine plankton RQs.…”
Section: Respiratory Quotientsmentioning
confidence: 93%